Loss of pSer2448‐mTOR expression is linked to adverse prognosis and tumor progression in ERG‐fusion‐positive cancers. Issue 6 (30th August 2012) - Müller, Julia; Ehlers, Arne; Burkhardt, Lia; Sirma, Hüseyin; Steuber, Thomas; Graefen, Markus; Sauter, Guido; Minner, Sarah; Simon, Ronald; Schlomm, Thorsten; Michl, Uwe
Abstract Prevalence and clinical significance of mammalian target of rapamycin (mTOR) phosphorylation at the serine 2448 is disputed in prostate cancer. A tissue microarray containing 3, 261 prostate cancers and 49 normal prostate samples with clinical follow‐up data was analyzed for pSer2448‐mTOR expression by immunohistochemistry. Moderate to strong pSer2448‐mTOR staining was found in all (n = 49) normal prostate tissues, but was lost in 24% or weak in 29% cancers. Moderate and strong staining was found in 36 and 11% of tumors. Loss of pSer2448‐mTOR staining was significantly linked to advanced stage (p = 0.0027), high‐grade (p = 0.0045), nodal positive cancers (p = 0.0483), early tumor recurrence (p < 0.0001, independently from stage and grade, p = 0.0016), lack of Ets‐related gene (ERG) fusion (p < 0.0001), reduced androgen receptor expression (p < 0.0001 each) and increased cell proliferation (p = 0.0092) in all cancers and in the subset of ERG‐fusion‐positive cancers. Loss of pSer2448‐mTOR expression was linked to tumor metastasis (p = 0.0275) in ERG‐fusion‐positive cancers only. Molecular subset analysis using pre‐existing phosphatase and tensin homolog (PTEN) deletion data revealed that loss of pSer2448‐mTOR expression is of prognostic relevance and defines a subpopulation of PTEN‐deleted and ERG‐fusion‐positive cancers with a particular poor outcome. The results of our study strongly suggest that loss of pSer2448‐mTOR expression is a marker for activated AKT/mTOR signaling. Tumors with concomitant PTEN deletion and activated mTOR signaling indicated by loss of pSer2448‐mTOR expression characterize a small (4%) but clinically significant subset of prostate cancers that might optimally benefit from anti‐mTOR therapies.